La médiatisation comme médiation de la restauration ? - Geneviève Reille-Taillefert (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
With two restoration cases, the author, wall painting’s conservator, try to explain the influence of the Medias on the people for the understanding and agreement of her work.